Naïve CD4+ T Cell Lymphopenia and Apoptosis in Chronic Hepatitis C Virus Infection Is Driven by the CD31+ Subset and Is Partially Normalized in Direct-Acting Antiviral Treated Persons - Auma, Ann W.N.; Shive, Carey L.; Lange, Alyssa; Damjanovska, Sofi; Kowal, Corinne; Zebrowski, Elizabeth; Pandiyan, Pushpa; Wilson, Brigid; Kalayjian, Robert C.; Canaday, David H.; Anthony, Donald D. (Frontiers in Immunology, 2021)
Background: The mechanisms underlying naïve CD4+ lymphopenia during chronic Hepatitis C Virus (HCV) infection are not well defined. Whether direct-acting antiviral (DAA) therapy restores peripheral naïve CD4+ T cell numbers and function has been unknown. Methods: We enumerated frequencies and counts of peripheral naïve CD4+, CD4+CD31+ and CD4+CD31- T cells by flow cytometry cross sectional analysis of chronic HCV infected (n=34) and DAA-treated persons (n=30) to age-range matched controls (n=25) and in a longitudinal cohort of HCV DAA treated persons (n=16) at 0, 4, 8 and 24 weeks after start of DAA. Cell apoptosis/survival (AnnexinV+7AAD+/BCL-2 staining) and cell cycle entry (Ki67 expression) of CD31+ and CD31- naïve CD4+ T cells was analyzed directly ex vivo and following 3 and 5 days of in vitro stimulation with interleukin (IL) -7 or CD3/CD28 activator, respectively. Results: In the cross-sectional cohort, naïve CD4+ proportions were lower in chronic HCV infected persons compared to controls and DAA-treated persons, and age was associated with naïve cell counts and proportions in HCV infected and treated persons as well. In the longitudinal cohort, naïve CD4+ proportions and counts increased 24 weeks after DAA therapy initiation, and this was localized to the CD4+CD31+ subset. Naïve CD4+ cell proportions negatively correlated with plasma levels of soluble CD14 following therapy in DAA-treated persons. Naïve CD4+ cells from HCV infected persons exhibited greater direct ex vivo apoptosis and cell-cycling (activation) compared to cells from DAA-treated persons and controls, and this was localized to the CD4+CD31+ subset. While there were no differences in expression of BCL-2 and IL-7 Receptor (CD127) at baseline, following IL-7 stimulation naïve CD4+CD31+ and CD4+CD31- T cells from HCV infected persons exhibited greater BCL-2 expression compared to cells from DAA-treated and control groups. Conclusions: Activation and apoptosis of peripheral naïve CD4+CD31+ T cells appear to contribute to naïve CD4+ lymphopenia in chronic HCV infection, and this defect is partially reversible with HCV DAA therapy. Age-associated naïve CD4+ lymphopenia is present both before and after HCV DAA therapy. These findings have implications for restoration of host immune function after DAA therapy.